Bacteria Inhibition: Detection and Inhibition of Bacteria on a Dual‐Functional Silver Platform (Small 3/2019). Issue 3 (18th January 2019) - Vedarethinam, Vadanasundari; Huang, Lin; Xu, Wei; Zhang, Ru; Gurav, Deepanjali D.; Sun, Xuming; Yang, Jing; Chen, Ruoping; Qian, Kun
Abstract : In article number1803051, Kun Qian and co‐workers construct a dual‐functional silver platform for the detection and inhibition of bacteria, toward real case applications and biological understandings. The designed platform achieves defined bioanalysis and targeted biotoxicity.